2013
DOI: 10.15282/jmes.5.2013.9.0060
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Activated Carbon (AC) Coir Fibers Reinforced with Epoxy Resin

Abstract: This research is to develop a carbon composite prepared from carbon coir fibers that is reinforced with epoxy resin. Carbon coir fibers were taken from three types of coir fiber specifically designated as CKCF, CYCF and CRCF. The samples were prepared using epoxy resin reinforced with carbon at different weight percentages for three types of coir fiber starting with 0wt.%, 2wt.%, 4wt.%, 6wt.%, 8wt.% and 10wt.%. The mechanical properties such as tensile stress and impact strength were used to characterize all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 13 publications
(9 reference statements)
0
16
0
Order By: Relevance
“…It is worth noting that using thermoset resin such as epoxy and polyester is strongly recommended as the matrix in developing natural fiber composites for structural applications [30]. Research into the feasibility of reinforcing epoxy or polyester with natural fibers has been reported in several literature [31][32][33][34]. A comprehensive theoretical framework for the new sandwich structure panel developed in this research under flexural loading was thoroughly discussed [35], while the statistical analysis of the flexural test was reported earlier [36].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that using thermoset resin such as epoxy and polyester is strongly recommended as the matrix in developing natural fiber composites for structural applications [30]. Research into the feasibility of reinforcing epoxy or polyester with natural fibers has been reported in several literature [31][32][33][34]. A comprehensive theoretical framework for the new sandwich structure panel developed in this research under flexural loading was thoroughly discussed [35], while the statistical analysis of the flexural test was reported earlier [36].…”
Section: Introductionmentioning
confidence: 99%
“…They found that true stress is directly linked to holding temperature and time [11]. Saleh et al [12] investigated the mechanical properties of composite materials by the tensile, impact, and creep tests and found that CKCF carbon composites have better mechanical properties in comparison of CRCF and CYCF carbon composites. Hariprasad et al [13] investigated the tensile and impact strengths of an alkali-treated banana-coir epoxy hybrid composite and found that tensile and impact strengths are more than untreated banana-coir epoxy hybrid composite, whereas the flexural strength of the untreated banana-coir epoxy hybrid composite was more.…”
Section: Introductionmentioning
confidence: 99%
“…The VCCT has been commonly employed by various researchers to simulate the mode III delamination of carbon/epoxy [6,[14][15][16] and glass/epoxy [3,5,[17][18][19][20] composite laminates. Nevertheless, in recent years, the CZM has gained its popularity in simulating the delamination behaviour of laminated composites.…”
Section: Introductionmentioning
confidence: 99%